2009
DOI: 10.1039/b907084b
|View full text |Cite
|
Sign up to set email alerts
|

Radiolysis of solvents containing C5-BTBP: identification of degradation products and their dependence on absorbed dose and dose rate

Abstract: Solvents intended for the separation of trivalent actinides from trivalent lanthanides in spent nuclear fuel have been irradiated with gamma-radiation. The solvents initially contained 0.005 M C5-BTBP dissolved in either hexanol or cyclohexanone and they were exposed to doses up to 20 kGy. Identification of degradation products was done using atmospheric pressure chemical ionization-mass spectrometry (APCI-MS). Structures were suggested for a number of degradation products and the relative intensity of the pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 22 publications
(22 reference statements)
5
52
0
Order By: Relevance
“…Heating 1 to 75°C in 15.5819 (7) 16.733 (1) 16.830 (1) 13.3034(7) b (Å) 11.1657 (5) 17.651 (1) 10.0546 (6) 17.3503(9) c (Å) 17.3224 (7) 17.077 (1) 103 (2) 88 (2) 173 (2) 143 (2) 143 (2) the presence of excess TEMPO also gave only 1 as the product. 1 H NMR spectroscopy revealed resonances consistent with Me-TEMPO as a byproduct. Complex 1 was definitively identified by X-ray crystallography, which revealed that it is an (η 1 -TEMPO) − complex (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Heating 1 to 75°C in 15.5819 (7) 16.733 (1) 16.830 (1) 13.3034(7) b (Å) 11.1657 (5) 17.651 (1) 10.0546 (6) 17.3503(9) c (Å) 17.3224 (7) 17.077 (1) 103 (2) 88 (2) 173 (2) 143 (2) 143 (2) the presence of excess TEMPO also gave only 1 as the product. 1 H NMR spectroscopy revealed resonances consistent with Me-TEMPO as a byproduct. Complex 1 was definitively identified by X-ray crystallography, which revealed that it is an (η 1 -TEMPO) − complex (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 88%
“…Colorless X-ray-quality crystals of 1 were grown from a hexane solution at −30°C (140 mg, 60%). 1 H NMR (C 6 D 6 ): δ 2.08 (s, 30H, C 5 Me 5 ), 1.39 (m, 4H, ONC 5 H 6 Me 4 ), 1.24 (m, 2H, ONC 5 H 6 Me 4 ), 1.14 (s, 12H, ONC 5 H 6 Me 4 ), 0.43 (s, 3H, Me). 13 (η 5 -C 5 Me 5 ) 2 Th(η 1 -C 3 H 5 )(η 3 -C 3 H 5 ) (2).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a solvent containing C5-BTBP received gradually increasing doses, the extraction of both actinides and lanthanides decreased substantially, making the molecule useless in a potential process. However, the radiolytic behavior of C5-BTBP containing solvents is interesting and has been further studied [4][5][6][7]. The extraction of americium (analogue for trivalent actinides) decreased more than the extraction of europium (analogue for trivalent lanthanides), resulting in a decrease of the separation factor [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the 6,6'-bis(5,6-dialkyl-1,2,4-triazin-3-yl)-2,2'-bipyridines (Cn-BTBPs, n = 1-5) were subjected to both acidic hydrolysis and radiolytic degradation by removal of their labile benzylic hydrogen atoms by free-radical species. [39] This led to the development of 6,6'-bis (5,5,8,8-tetramethyl-5,6,7,8-tetrahydro-1,2,4-benzotriazin-3-yl)-2,2-bipyridine (CyMe 4 -BTBP) 3 ( Figure 1) in which the benzylic hydrogens have been removed. [40] To date this ligand is the most promising for use in a future SANEX process and in a counter-current 'hot-test' using laboratory centrifugal contactors, 99.9 % of the actinides were removed from the feed solution in a 16-stage flowsheet with very high decontamination factors for Am (7,000) and Cm (1,000).…”
Section: Introductionmentioning
confidence: 99%